Mosquito‐Borne Diseases in Canada: Integrated Perspectives on Disease Management and Influences of Environmental and Anthropogenic Factors Affecting the Transmission Cycle - Antoinette Ludwig; David Lapen (Public Health Challenges)
ABSTRACT Globally, mosquito‐borne diseases (MBD) cause the highest morbidity and mortality in humans and animals. Currently, in Canada, endemic MBDs that are significant public health problems are all zoonoses and are caused primarily by West Nile virus, Eastern equine encephalitis virus, and Californian serogroup viruses, including the Jamestown Canyon and the Snowshoe hare viruses. The transmission cycles of these viruses are changing, linked to global population movements (including vectors) and climate and land use changes. Here, we present the state of knowledge, related to MBDs in Canada, as well as salient surveillance approaches carried out to monitor them and their infection rates. We propose a few theoretical and operational research avenues in order to improve our understanding of transmission cycle changes, as well as the potential of new surveillance tools such as citizen science, metagenomics, artificial intelligence, and remote sensing to help reduce disease burdens on Canadians. This will support public and animal health responses to these zoonoses and help proactively manage such diseases under changing environmental conditions.